(untitled) (Bangladesh Journal of Medical Microbiology, 2025)
Background: Community-acquired pneumonia (CAP) is an acute respiratory illness responsible for significant morbidity and mortality globally. Objective: The objective of this study was to detect the common causative bacterial agents of CAP and their antimicrobial sensitivity pattern and also to detect the DNA of Streptococcus pneumoniae, Haemophilus influenzae, Mycoplasma pneumoniae, Chlamydia pneumoniae, Legionella pneumophila, Staphylococcus aureus and Moraxella catarrhalis from sputum sample by multiplex real-time PCR. Methodology: This cross-sectional observational study was carried out in the Department of Microbiology, Chittagong Medical College, Chattogram from July 2019 to June 2020. A total of 87 sputum samples were collected from CAP patients. Common causative bacterial agents of pneumonia were detected by gram staining, culture, biochemical tests, and multiplex real-time PCR of sputum. Results: In this study, among 87 CAP patients’ age was in the range of 12 years to 85 years with the mean age being 55.09 (±18.74) years. Bacterial isolation was determined in 33 (37.9%) of all patients with the culture method, this number increased up to 48 (55.2%) with multiplex real-time PCR. The bacteria most commonly identified by multiplex real-time PCR were Streptococcus pneumoniae 20(41.7%), Haemophilus influenzae 12(25.0%) and Staphylococcus aureus 11(22.9%). The most frequent bacteria found in the culture was Pseudomonas species 11(33.3%), followed by Staphylococcus aureus 10(30.3%), Klebsiella species 7(21.2%), Streptococcus pneumoniae 4(12.1%) and Escherichia coli 1(3.1%). Regarding antibiotic sensitivity patterns Meropenem and Clarithromycin were the most sensitive drug both in Gram-positive and Gram-negative organisms. Cefixime and azithromycin were the most resistant drug in both groups. Considering culture as the gold standard the sensitivity of PCR was 100%, the specificity was 80.72%, positive predictive value (PPV) was 20.0% and negative predictive value (NPV) was 100.0 % and the accuracy was 81.61%. Out of 87 patients, 51(58.3%) sputum samples were positive by Gram staining. In Gram-stain-positive cases, the most frequently detected bacteria were Gram-negative bacilli 24(27.1%), followed by Gram-positive cocci 12 (13.72%), Gram-negative coccobacillus 7(8.0%), Gram-positive diplococci 4(4.5%) and mixed type 4 (4.5%). Conclusion: In conclusion multiplex real-time PCR was highly sensitive, specific, and superior to other conventional methods for the detection of bacterial pathogens in the sputum of CAP patients. Bangladesh Journal of Medical Microbiology, January 2025;19 (1):10-17